Porto sinusoidal vascular disease: an unusual cause of digestive bleeding - Yance, Stalin (2024)
Portal hypertension (PHT) is defined as an increase in pressure at the level of the portal vein above 5 mmHg, the most common cause being liver cirrhosis. Among the presinusoidal intrahepatic causes of PHT with portal venular involvement, what was traditionally known as idiopathic non-cirrhotic portal hypertension (NCIH) is described, with the requirements of excluding those patients who did not present PHT, as well as those with the presence of liver cirrhosis and thrombosis. portal venous vein (PVT). Currently, the diagnostic criteria for this entity have been reconsidered, and its name, being known as porto-sinusoidal vascular disease (PSVD), also does not exclude patients with  PHT or the presence of underlying liver disease. Liver biopsy continues to be the gold standard for diagnosis. The clinical manifestations are derived from PHT and the management is similar to the complications that occur in patients with liver cirrhosis. The case of a male patient is presented who presents with symptoms of digestive bleeding, with findings of esophageal varices in upper endoscopy in addition to a study of viral, autoimmune liver disease and negative deposits, with a conclusive liver biopsy of porto-sinusoidal vascular disease.